Academic Administration of School Administrators under the Prachinburi Primary Educational Service Area Office 2 - สิทธิพล, ศิริรัตน์; ประวัติรุ่งเรือง, ปราศรัย; แก้วมงคล, ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The purposes of this research were: (1) to study the level of academic administration of school administrators under the Prachinburi Primary Educational Service Area Office 2; (2) to compare teachers’ opinions toward academic administration, classified by gender, educational level, work experience, and school size; and (3) to explore guidelines for academic administration. The sample consisted of 298 teachers working in schools under the Prachinburi Primary Educational Service Area Office 2. The sample size was determined using the Krejcie and Morgan (1970) table, and stratified random sampling was employed. The research instrument was a five-point rating scale questionnaire with an Index of Item-Objective Congruence (IOC) ranging from 0.80 to 1.00 and a reliability coefficient of 0.93. The statistical methods used for data analysis included mean, standard deviation, t-test, and F-test One-way ANOVA.           The research findings were as follows: 1. The overall and individual aspects of academic administration were at a high level. The highest mean score was found in the development of instructional media, innovation, and educational technology, followed by learning management process development and curriculum development, respectively. 2. The comparison of teachers’ opinions revealed no statistically significant differences at the .05 level when classified by gender, educational level, work experience, and school size. 3. The guidelines for academic administration indicated that school administrators play a crucial role as instructional leaders, emphasizing participation from all stakeholders, systematic development, and the application of technology to enhance the quality of learning management and students’ academic achievement sustainably. Emphasis should be placed on collaboration among teachers, communities, and parents, the use of learning standards as a foundation for active learning management, appropriate use of media and technology, supportive supervision, and continuous professional development of teachers to sustainably improve educational quality.